Pelatihan Penulisan Penelitian Tindakan Kelas (PTK) pada Guru Sekolah Dasar di Kecamatan Sukun Kota Malang - Heriyawati, Dwi Fita; Sari, Ifit Novita (Amalee: Indonesian Journal of Community Research and Engagement, 2020)
This article describes the results of community service by the engagement team of Islamic University of Malang which is conducted toward the teachers of an elementary school in Sukun District, Malang City. The program aims to improve the teachers’ ability in writing research in particular using the classroom action research (CAR) method of which conducting the report always became the difficulty for them. Therefore, in this occasion we identify the problems as follows: a) deciding the topic for the CAR, b) creating the title for the research, c) creating research questions, d) creating the stages of the research and also relevant instrumentation to collect the data, e) writing discussion for the results, then composing the suggestion and conclusion from the results. The method of implementing community service is done by carrying out training and practice of writing CAR. From the results of the training, found that it were quite good where elementary school teachers gained experience about writing CAR. The participants were very enthusiastic about the training, so in the end of this activity, it is expected that by conducting this CAR training, they will be able to conduct the research both independently and in groups. Keywords: CAR, mentoring, training Abstrak Artikel ini menjelaskan hasil pengabdian masyarakat oleh tim pengabdi dari Universitas Islam Malang yang dilakukan terhadap guru-guru Sekolah Dasar di Kabupaten Sukun, Kota Malang. Pengabdian ini bertujuan untuk meningkatkan kemampuan guru dalam menulis penelitian khususnya menggunakan metode penelitian tindakan kelas (PTK) yang mana melakukan laporan selalu menjadi kesulitan bagi mereka. Oleh karena itu, dalam kesempatan ini kami mengidentifikasi masalah sebagai berikut: a) memutuskan topik untuk CAR, b) membuat judul, c) membuat pertanyaan penelitian, d) menciptakan tahapan penelitian dan juga instrumentasi yang relevan untuk mengumpulkan data, e) menulis diskusi hasil, kemudian menyusun saran dan kesimpulan dari hasil. Metode pelaksanaan pengabdian masyarakat dilakukan dengan melakukan pelatihan dan praktik penulisan PTK. Dari hasil pelatihan, ditemukan bahwa guru Sekolah Dasar memperoleh pengalaman tentang menulis PTK. Para peserta sangat antusias dengan pelatihan ini, sehingga pada akhir kegiatan ini, diharapkan dengan melakukan pelatihan PTK ini, mereka akan dapat melakukan penelitian baik secara mandiri maupun dalam kelompok. Kata Kunci: pelatihan, pendampingan, PTK